2018
DOI: 10.1175/mwr-d-17-0386.1
|View full text |Cite
|
Sign up to set email alerts
|

High-Altitude (0–100 km) Global Atmospheric Reanalysis System: Description and Application to the 2014 Austral Winter of the Deep Propagating Gravity Wave Experiment (DEEPWAVE)

Abstract: A data assimilation system (DAS) is described for global atmospheric reanalysis from 0- to 100-km altitude. We apply it to the 2014 austral winter of the Deep Propagating Gravity Wave Experiment (DEEPWAVE), an international field campaign focused on gravity wave dynamics from 0 to 100 km, where an absence of reanalysis above 60 km inhibits research. Four experiments were performed from April to September 2014 and assessed for reanalysis skill above 50 km. A four-dimensional variational (4DVAR) run specified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 77 publications
5
89
0
Order By: Relevance
“…Zonal and meridional winds measured by the meteor radar at Kingston, Tasmania, and obtained from the NAVGEM T119L74 reanalysis (Eckermann et al, ) from 03 to 09 UT on 13 July centered on Lauder are shown in Figures b and c. The differences between the radar and reanalysis winds above ~80 km likely reflect the 23° of longitude and 2° of latitude separation between the two sites, as well as the inference of a large semidiurnal tide at these latitudes on 13 July measured by the meteor radar and implied by NAVGEM reanalysis.…”
Section: Flight Planning Meteorological Conditions and Background Fmentioning
confidence: 87%
“…Zonal and meridional winds measured by the meteor radar at Kingston, Tasmania, and obtained from the NAVGEM T119L74 reanalysis (Eckermann et al, ) from 03 to 09 UT on 13 July centered on Lauder are shown in Figures b and c. The differences between the radar and reanalysis winds above ~80 km likely reflect the 23° of longitude and 2° of latitude separation between the two sites, as well as the inference of a large semidiurnal tide at these latitudes on 13 July measured by the meteor radar and implied by NAVGEM reanalysis.…”
Section: Flight Planning Meteorological Conditions and Background Fmentioning
confidence: 87%
“…These observations came from bias‐corrected Version 4.2 MLS temperatures, Version 2.0 temperature retrievals from the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) instrument on NASA's TIMED satellite, and O 2 microwave radiances from the Special Sensor Microwave Imager/Sounder (SSMIS) on three separate satellites (F17, F18, and F19) of the Defense Meteorological Satellite Program. The fields used here correspond to a reanalysis run using hybrid ensemble/4DVAR (four‐dimensional variational) data assimilation at a T119L74 outer‐loop (T47L74 inner‐loop) resolution (see Eckermann et al, , for details). For the present work, these reanalyses were reinterpolated onto a pressure grid with a constant pressure‐height resolution of 1 km, and from the quadratic Gaussian grid onto a regular 1° × 1° global grid.…”
Section: Data and Analysis Methodsmentioning
confidence: 99%
“…The calculated T ′ from mixing ratio contours for each pass are shown in Figure . The background d trueT¯/ dz used in equation was obtained from NAVGEM reanalysis (Eckermann et al, ), reinterpolated onto a constant geometric height grid for the 13 July 2014 flight. The temperature profile was the average of all reanalysis grid points within a circular region centered near Mt.…”
Section: Temperature and Mf Measurements And Validationmentioning
confidence: 99%